Simulation and Modeling of a Five -Level (NPC) Inverter Fed by a Photovoltaic Generator and Integrated in a Hybrid Wind-PV Power System - Rezki, M.; Griche, I. (Engineering, Technology & Applied Science Research, 2017)
A distributed hybrid coordinated wind photovoltaic (PV) power system was proposed in this paper. As oil and coal reserves are being depleted whilst at the same time the energy demand is growing, it is important to consider alternative energy generating techniques. Today, the five-level (NPC) inverter represents a good alternative for several industrial applications. To take advantage of the five-level inverter topology and the benefits of renewable energy represented by a photovoltaic generator, a new scheme of these controllers is proposed in this work. This paper outlines the design of a hybrid power system consisting of a solar photovoltaic (PV) and a wind power system. The system is modeled in Matlab Simulink and tested for various conditions. The model and results are discussed in this paper.